2005
DOI: 10.1038/labinvest.3700240
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for megalin-mediated proximal tubular uptake of L-FABP, a carrier of potentially nephrotoxic molecules

Abstract: Liver-type fatty acid binding protein (L-FABP) binds with high affinity to hydrophobic molecules including free fatty acid, bile acid and bilirubin, which are potentially nephrotoxic, and is involved in their metabolism mainly in hepatocytes. L-FABP is released into the circulation, and patients with liver damage have an elevated plasma L-FABP level. L-FABP is also present in renal tubules; however, the precise localization of L-FABP and its potential role in the renal tubules are not known. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…In the kidney, there are receptors and transporters such as sodium/glucose co-transporter-2 and organic cation transporter 2, which have been reported that testosterone changed their expression levels in rats (Pávó et al, 1995;Urakami et al, 2000;Ljubojevic et al, 2004;Sabolic et al, 2012;Loh et al, 2017). Meanwhile, sex differences of megalin and cubilin, receptors related to reabsorption of LMWPs and albumin which are localized in the renal proximal tubules (Cui et al, 1996;Orlando et al, 1998;Birn et al, 2000;Oyama et al, 2005;Hvidberg et al, 2005;Kaseda et al, 2007;Amsellem et al, 2010), have been ambiguous. It might be possible that one or more receptors and transporters contributing to reabsorption of LMWPs and albumin were affected by testosterone, and their excretion levels had varied.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, there are receptors and transporters such as sodium/glucose co-transporter-2 and organic cation transporter 2, which have been reported that testosterone changed their expression levels in rats (Pávó et al, 1995;Urakami et al, 2000;Ljubojevic et al, 2004;Sabolic et al, 2012;Loh et al, 2017). Meanwhile, sex differences of megalin and cubilin, receptors related to reabsorption of LMWPs and albumin which are localized in the renal proximal tubules (Cui et al, 1996;Orlando et al, 1998;Birn et al, 2000;Oyama et al, 2005;Hvidberg et al, 2005;Kaseda et al, 2007;Amsellem et al, 2010), have been ambiguous. It might be possible that one or more receptors and transporters contributing to reabsorption of LMWPs and albumin were affected by testosterone, and their excretion levels had varied.…”
Section: Discussionmentioning
confidence: 99%
“…The primary function of FABP is the facilitation of long-chain free fatty-acid transport from the plasma membrane to sites for oxidation (mitochondria, peroxisomes) (Oyama et al, 2005;Pelsers et al, 2005). Two types of FABP have been identified in the human kidney, liver-type FABP (L-FABP) in the proximal tubule and heart-type FABP (H-FABP) in the distal tubule (Maatman et al, 1991;Maatman et al, 1992).…”
Section: Fatty Acid Binding Protein (Fabp)mentioning
confidence: 99%
“…Fatty acid binding proteins are a family of small, highly conserved carrier proteins that bind long-chain fatty acids and other hydrophobic ligands. This protein can also be found outside the cell and is able to bind bile acids (48). It is thought that the roles of fatty acid binding proteins include fatty acid uptake, transport, and metabolism and are regulated by liver-enriched transcription factors HNF3␤ and C/EBP␣ (49).…”
Section: Discussionmentioning
confidence: 99%